Evaluation of acetylcholinesterase source from fish, Tor tambroides for detection of carbamate - Siti Aqlima Ahmad; Mohd Khalizan Sabullah; Nor Aripin Shamaan; Mohd Yunus Abd. Shukor; Hussain Jirangon; Ariff Khalid; Mohd Arif Syed (Triveni Enterprises, 2016)
Acetylcholinesterase (AChE) from the brain tissue of local freshwater fish, was isolated through affinity purification. Acetylthiocholine iodide (ATCi) was preferable synthetic substrate to purified AChE with highest maximal velocity (V ) and lowest biomolecular constant (K ) at 113.60 Umg and 0.0689 mM, respectively, with highest catalytic efficiency ratio (V /K ) of 1648.77. The optimum pH was 7.5 with sodium phosphate buffer as medium, while optimal temperature was in the range of 25 to 35 °C. Bendiocarp, carbofuran, carbaryl, methomyl and propoxur significantly lowered the AChE activity greater than 50%, and the IC value was estimated at inhibitor concentration of 0.0758, 0.0643, 0.0555, 0.0817 and 0.0538 ppm, respectively.